Disease Status of Afghan Refugees and Migrants in Pakistan - Malik, Muhammad Suleman; Afzal, Muhammad; Farid, Alveena; Khan, Fati Ullah; Mirza, Bushra; Waheed, Mohammad Tahir (Frontiers in Public Health, 2019)
World is facing the largest refugee crisis of its time due to continuously outgoing wars, conflicts and natural disasters. One of the important aspects of refugees and migrants is health. Till date, no comprehensive data was available related to health status of Afghan refugees and internally displaced persons (IDPs) in Pakistan. Here, we present health status for Afghan refugees for last seven years and for IDPs for 2-4 years. For Afghan refugees the data was provided by Commissionerate Afghan Refugee (CAR), Pakistan, whereas data for IDPs was collected from hospitals and Basic health units (BHUs) of different districts of Khyber Pakhtunkhwa namely Peshawar, Dera Ismail Khan and Bannu. Highest number of Afghan refugee’s deaths occurred due to cardiovascular problems. Most prevalent reported infections were respiratory tract infections (48.05%). Skin diseases and Diarrhea collectively affected 21.08% of Afghan refugees. Overall, disease burden was more in females than males in Afghan refugee’s population. To the best of our knowledge, this is the first comprehensive report on health and disease status of Afghan refugees and IDPs in Pakistan.